The Impact of Interaction Design on Student Engagement in E-Learning - Djuwari, Djuwari; Meilina, Herlina; Suroyo, Suroyo; Raihana, Esti; Maisarah, Maisarah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The growing reliance on e-learning platforms has highlighted the importance of interaction design in shaping student engagement and learning outcomes. Poorly designed digital learning environments often lead to low motivation, decreased participation, and reduced retention rates. Ensuring that interaction design effectively supports student engagement is essential for optimizing online learning experiences. This study aims to examine the impact of interaction design elements, including navigation structure, multimedia integration, and user experience, on student engagement in e-learning environments. A mixed-methods approach was employed, combining a usability assessment of e-learning platforms, student engagement surveys, and instructor interviews. Findings indicate that intuitive navigation, interactive multimedia, and real-time feedback mechanisms significantly enhance student participation and learning satisfaction. Statistical analysis revealed a strong correlation between well-designed interaction features and improved student retention rates. The study concludes that incorporating user-centered interaction design principles in e-learning platforms enhances engagement and contributes to more effective learning experiences. Future research should explore adaptive and AI-driven interaction design models to further optimize student-centered digital learning environments.